The Influence of Internshıp Experıence and Career Decısıon-Makıng Self-Effıcacy on Job Readıness (A Study on Internshıp Partıcıpants and Independent Study Certıfıed Under Kampus Merdeka) - Sijabat, Elysa Laura Octavia; Dodi Wirawan Irawanto; Ayomi, Marveys (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
The fact that demographic bonus presents a major opportunity for a country’s growth and development if the working-age population, especially youth and university graduates, can be effectively absorbed into the labor market. In Indonesia, the gap between students’ skills and labor market needs remains a key factor underlying the relatively high unemployment rate among graduates. Consequently, strengthening students’ work readiness is crucial. This study examines the influence of internship experience and career decision-making self-efficacy on the work readiness of students participating in the Certified Internship and Independent Study Program (MSIB) of Kampus Merdeka. This explanatory quantitative research involved 389 respondents selected through survey using purposive sampling, targeting active Indonesian university students from the 2020–2022 cohorts who participated in the 5th to 7th batches of the Certified Internship program. Data were analyzed using multiple linear regression with SPSS version 30. The results show that both internship experience and career decision-making self-efficacy have a positive and significant effect on work readiness, both partially and simultaneously. These findings imply that the better the students’ internship experience and career decision-making self-efficacy, the higher their level of work readiness. The study highlights the importance for higher education institutions and policymakers of enhancing internship quality and fostering students’ career decision-making self-efficacy to strengthen their readiness to enter the workforce.